Developing Border Area: A Study of the Village Internet Program in Kaliau Village, Sambas Regency - Arifin, Arifin; Yuniarsih, Rulida (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2022)
The implementation of the village community empowerment program around the national border areas is faced a unique environment with complex problems. The purpose of the study is to highlight the empowerment program and explore the supporting and inhibiting factors of the program. The type of this study was descriptive-qualitative. Data were collected through interviews, document searches, and observation. The collected data were then processed, analysed, and concluded. Results showed that the process of implementing the empowerment program started from with planning the program carried out by the village government and the community. Program planning was conducted using a bottom-up pattern, involving representatives from each community component. The program implementation was based on the bottom-up planning model as the main supporting factor for the effectiveness of the empowerment program. Through the program implemented, all components of society can meet their needs regarding internetbased information. The main obstacles to implementing the empowerment program are natural matters, such as wide-area coverage, uneven distribution of the population, and lack of resources for the program development. The success of the program can be achieved through community involvement in program planning based on full awareness of the community’s needs for the program and structurally supported by the village government.